2010
DOI: 10.1107/s0021889810025379
|View full text |Cite
|
Sign up to set email alerts
|

Structure of water-based ferrofluids with sodium oleate and polyethylene glycol stabilization by small-angle neutron scattering: contrast-variation experiments

Abstract: Contrast variation in small‐angle neutron scattering (SANS) experiments is used to compare the structures of a water‐based ferrofluid, where magnetite nanoparticles are stabilized by sodium oleate, and its mixture with biocompatible polyethylene glycol, PEG. The basic functions approach is applied, which takes into account the effects of polydispersity and magnetic scattering. Different types of stable aggregates of colloidal particles are revealed in both fluids. The addition of PEG results in a reorganizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…The obtained results are consistent with the analysis of the interaction of PEG with SO-coated magnetite nanoparticles in water-based magnetic fluids [8], where the structure reorganization of the particle aggregates at sufficiently high PEG content was explained by the formation of the "polymer layer" around colloidal particles as a result of partial replacement of SO with PEG on the surface of magnetite.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The obtained results are consistent with the analysis of the interaction of PEG with SO-coated magnetite nanoparticles in water-based magnetic fluids [8], where the structure reorganization of the particle aggregates at sufficiently high PEG content was explained by the formation of the "polymer layer" around colloidal particles as a result of partial replacement of SO with PEG on the surface of magnetite.…”
Section: Resultssupporting
confidence: 79%
“…Here, we are concerned with the interaction of PEG with SO micelles in water under the conditions characteristic for the previously studied magnetic fluids [8]. Specifically, we investigated aqueous micelle solutions of SO in a concentration range of 1 -8.5 wt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scattering form factor of the coils is well described by the Debye formula over the whole measured q-interval at the PEG concentration below 2%. High adsorption properties of PEG for various substrates [5][6][7] and nanoparticles [8] also suggest a developed structure of this polymer.…”
Section: Resultsmentioning
confidence: 99%
“…A magnetic fluid-magnetite particles coated with sodium oleate and PEG-was formed in this way [8]. Infrared spectroscopy and digital scanning calorimetry measurements showed that after such a procedure, PEG adsorbs on the magnetite [8,9]. All samples contained the same amount of PEG-20.69 mg per mL of magnetic fluid.…”
Section: Sample Preparationmentioning
confidence: 99%